Tissue Factor-Negative Cell-Derived Microparticles Play a Distinctive Role in Hemostasis: A Viewpoint Review - Horstman, Lawrence L.; McCauley, Robert F.; Jy, Wenche; Ahn, Yeon S. (Seminars in Thrombosis and Hemostasis, 2019)
Circulating cell-derived microparticles (MPs) exhibit procoagulant activity and have been investigated for a possible role in some human pathologies. However, their potential role in hemostasis has been neglected and often denied. This review brings to attention a specific body of direct clinical evidence supporting an important but distinctive role of MPs in hemostasis. Evidence for a role of MPs in hemostasis includes: (1) two congenital bleeding disorders attributed to impaired release of MPs; (2) two recent studies of trauma patients relating naturally elevated endogenous MPs at admission to reduced transfusion requirements and better outcomes; (3) a study of coronary surgery patients showing that elevated MP before surgery reduces transfusion requirements during surgery; and (4) a clinical study of patients with immune thrombocytopenia demonstrating that those with high circulating MP have reduced bleeding compared to patients with similar platelet counts but lower MP levels. Mechanisms involving potentiating the contact factor pathway are thought to play a key role and are probably synergistic with polyphosphate released from activated platelets at sites of endothelial injury. Hemostatic defect of patients with deficient MP-mediated coagulation resembles deficiency of FXI (hemophilia C), distinct from hemophilia A or B, so can be termed type C hemostasis. A better understanding of this proposed hemostatic pathway may lead to improved methods for controlling excessive bleeding in surgery, trauma, and other clinical settings.
Keywords: cell-derived microparticles; extracellular vesicles; hemostasis; contact pathway; coagulation